Trends in the Electron Microscopy Data Bank (EMDB). Issue 6 (5th June 2017) - Patwardhan, Ardan
Abstract : The Electron Microscopy Data Bank (EMDB), the public archive for three‐dimensional EM reconstructions, is an invaluable resource for obtaining a birds‐eye view of trends affecting the field of cryo‐EM. EMDB is growing rapidly, with almost a quarter of the entries having been released over the past year. Abstract : Recent technological advances, such as the introduction of the direct electron detector, have transformed the field of cryo‐EM and the landscape of molecular and cellular structural biology. This study analyses these trends from the vantage point of the Electron Microscopy Data Bank (EMDB), the public archive for three‐dimensional EM reconstructions. Over 1000 entries were released in 2016, representing almost a quarter of the total number of entries (4431). Structures at better than 6 Å resolution now represent one of the fastest‐growing categories, while the share of annually released tomography‐related structures is approaching 20%. The use of direct electron detectors is growing very rapidly: they were used for 70% of the structures released in 2016, in contrast to none before 2011. Microscopes from FEI have an overwhelming lead in terms of usage, and the use of the RELION software package continues to grow rapidly after having attained a leading position in the field. China is rapidly emerging as a major player in the field, supplementing the US, Germany and the UK as the big four. Similarly, Tsinghua University ranks only second to the MRC Laboratory for Molecular Biology in terms of involvement in publications associated with cryo‐EM structures at better than 4 Å resolution. Overall, the numbers point to a rapid democratization of the field, with more countries and institutes becoming involved.